The Effect of the Orientation, Analysis, Synthesis, Investigation, Synergy (OASIS) Model on Students' Cognitive Learning Outcomes in Kinetic Gas Theory - Sasmita, Yopi Wiliyana; Aripin, Aripin; Makiyah, Yanti Sofi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Based on the results of a preliminary study at SMA Negeri 1 Cihaurbeuti, it is known that students' cognitive learning outcomes are still classified as poor, one of which is the kinetic gas theory material which still has not reached the minimum completeness criteria, namely 70, because the learning method still uses the lecture method. Apart from that, the lack of innovation in the use of models in physics learning causes physics learning to become less interesting for students so that cognitive learning outcomes need to be improved. One of the solutions taken by researchers to overcome this problem is to apply the Orientation, Analysis, Synthesis, Investigation, Synergy (OASIS) learning model. The aim of this research is to analyze the influence of the OASIS learning model on students' cognitive learning outcomes in class XI gas kinetic theory material at SMA Negeri 1 Cihaurbeuti. The research method used is quasi experimental design because this research is educational research with the object used being humans. The research design applied is nonequivalent control group design, where the two classes of research samples will undergo tests before and after being given treatment. The population in this research is all 7 classes of class To measure cognitive learning outcomes (C1, C2, C3), students were tested before treatment (pretest) and after being given treatment (posttest) in the form of a description of 6 questions on the main material of the kinetic theory of gases. The data analysis technique that will be used is the prerequisite test including the normality test and homogeneity test, as well as hypothesis testing using the t test with a significance level  showing that  (4.06>1.67) which means  is accepted and  is rejected, so it can be concluded that the OASIS learning model has an effect on students' cognitive learning outcomes in gas kinetic theory material.